Stability of magnesiowüstite in Earth's lower mantle - Lin, Jung-Fu (The National Academy of Sciences, 2003)
Magnesiowüstite [(Mg,Fe)O] is the second most abundant mineral of Earth's lower mantle. Understanding its stability under lower mantle conditions is crucial for interpreting the physical and chemical properties of the whole Earth. Previous studies in an externally heated diamond anvil cell suggested that magnesiowüstites decompose into two components, Fe-rich and Mg-rich magnesiowüstites at 86 GPa and 1,000 K. Here we report an in situ study of two magnesiowüstites [(Mg(0.39),Fe(0.61))O and (Mg(0.25),Fe(0.75))O] at pressures and temperatures that overlap with mantle conditions, using a laser-heated diamond anvil cell combined with synchrotron x-ray diffraction. Our results show that addition of Mg in wüstite (FeO) can stabilize the rock-salt structure to much higher pressures and temperatures. In contrast to the previous studies, our results indicate that Mg-rich magnesiowüstite is stable in the rock-salt structure in the lower mantle. The physical and chemical properties of magnesiowüstite should change gradually and continuously in the lower mantle, suggesting that it does not make a significant contribution to seismic-wave heterogeneity of the lower mantle. Stable Mg-rich magnesiowüstite in lowermost mantle can destabilize FeO in the core–mantle boundary region and remove FeO from the outer core.